2020
DOI: 10.1021/acs.jproteome.0c00387
|View full text |Cite
|
Sign up to set email alerts
|

“A Chain Only as Strong as Its Weakest Link”: An Up-to-Date Literature Review on the Bidirectional Interaction of Pulmonary Fibrosis and COVID-19

Abstract: The COVID-19 pandemic rapidly became a worldwide healthcare emergency affecting millions of people, with poor outcomes for patients with chronic conditions and enormous pressure on healthcare systems. Pulmonary fibrosis (PF) has been cited as a risk factor for a more severe evolution of COVID-19, primarily because its acute exacerbations are already associated with high mortality. We reviewed the available literature on biochemical, pathophysiological, and pharmacological mechanisms of PF and COVID-19 in an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 148 publications
(311 reference statements)
0
33
0
1
Order By: Relevance
“…One of the most important pathological changes was mechanization of alveolar exudate and interstitial lung fibrosis [4] , [5] . Pulmonary fibrosis (PF) was closely related to tissue inflammation and damage repair, which has been characterized as a risk factor for a more severe evolution and higher mortality of COVID-19 [6] , [7] , [8] , [9] . Also, patients recovering from severe and critical COVID-19 disease are at serious risk of developing postinflammatory PF through the follow-up computed tomography (CT) scan [4] , [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important pathological changes was mechanization of alveolar exudate and interstitial lung fibrosis [4] , [5] . Pulmonary fibrosis (PF) was closely related to tissue inflammation and damage repair, which has been characterized as a risk factor for a more severe evolution and higher mortality of COVID-19 [6] , [7] , [8] , [9] . Also, patients recovering from severe and critical COVID-19 disease are at serious risk of developing postinflammatory PF through the follow-up computed tomography (CT) scan [4] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been currently accepted that Krebs von den Lungen-6 (KL-6), a glycoprotein secreted by type II alveolar pneumocytes and bronchiolar epithelial cells, is a biomarker of several interstitial lung diseases (ILD), including idiopathic pulmonary fibrosis [11] , [12] , [13] . A recent study reported that there is a complexity of interactions between coexisting idiopathic pulmonary fibrosis/ILD and COVID-19 disease [6] . Serum KL-6 has been suggested to be a useful biomarker for evaluating the severity of COVID-19, however, the results from another research did not demonstrate that KL-6 can discriminate different ventilatory phenotypes in COVID-19 patients [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been reported in the literature that equal than other coronaviruses are responsible for producing pulmonary fibrosis [ 38 , 39 , 40 , 41 ], and that this has also been recognized as a sequel to acute respiratory distress syndrome (ARDS). Also, dyspnea related with COVID-19 can be associated with heart problems [ 42 , 43 ], so its origin should be investigated, and recovered patients should be followed up, since the extent of the complications is still unknown [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific terminology here can create confusion, and clarification of "post-COVID-19 PF" is needed, as it is often used interchangeably to refer to one of the following: post-acute respiratory distress syndrome (ARDS) PF [13], post-inflammatory PF [4], post-viral PF, and post-viral ILD. The etiology, prognosis and progression of post-viral PF syndromes may differ from fibrotic ILDs like IPF [14].…”
Section: Definition and Classification Of Interstitial Lung Disease (Ild)mentioning
confidence: 99%